Response of Core Microbial Consortia to Chronic Hydrocarbon Contaminations in Coastal Sediment Habitats - Jeanbille, Mathilde; Gury, Jérôme; Duran, Robert; Tronczynski, Jacek; Agogué, Hélène; Ben Saïd, Olfa; Ghiglione, Jean-François; Auguet, Jean-Christophe (Frontiers in Microbiology, 2016)
Traditionally, microbial surveys investigating the effect of chronic anthropogenic pressure such as polyaromatic hydrocarbons (PAHs) contaminations consider just the alpha and beta diversity and ignore the interactions among the different taxa forming the microbial community. Here, we investigated the ecological relationships between the three domains of life (i.e. Bacteria, Archaea and Eukarya) using 454 pyrosequencing data of the 16S rRNA and 18S rRNA genes from chronically impacted and pristine sediments, along the coasts of the Mediterranean Sea (Gulf of Lion, Vermillion coast, Corsica, Bizerte lagoon and Lebanon) and the French Atlantic Ocean (Bay of Biscay and English Channel). Our approach provided a robust ecological framework for the partition of the taxa abundance distribution into 859 core OTUs and 6629 satellite OTUs. OTUs forming the core microbial community showed the highest sensitivity to changes in environmental and contaminant variations, with salinity, latitude, temperature, particle size distribution, total organic carbon (TOC) and PAH concentrations as main drivers of community assembly. The core communities were dominated by Gammaproteobacteria and Deltaproteobacteria for Bacteria, by Thaumarchaeota, Bathyarchaeota and Thermoplasmata for Archaea and Metazoa and Dinoflagellata for Eukarya. In order to find associations among microorganisms, we generated a co-occurrence network in which PAHs were found to impact significantly the potential predator – prey relationship in one microbial consortium composed of ciliates and Actinobacteria. Comparison of network topological properties between contaminated and non-contaminated samples showed substantial differences in the structure of the network and indicated a higher vulnerability to environmental perturbations in the contaminated sediments.